Antonio Garbasso, Dantean and Guelph physicist - Mazzoni, Massimo (Il Colle di Galileo, 2023)
Antonio Garbasso, a physicist from Piedmont but Tuscan by adoption, was a scientist with a multitude of interests. He played a decisive role in the panorama of Italian physics in the early decades of the 20th century but was also active in humanities and studied Dante’s works, focusing particularly on their scientific content. The article examines some of his public lectures on the Poet and draws a profile of the man.